Studies on the Comparative Growth and Establishment of Aoaoia Tortilis (Forsk) and Aoaoia Senegal in Rocky Habitats - Puri, D N; Muthana, K D; Handa, D P; Singh, Mahinder (Annals of Arid Zone, 2016)
One year old nursery raised seedlings of Acacia tortilis, (from Israel) and Acacia senegal (local), when tried in specially prepared pits, have proved to be of much promise for afforesting rocky habitats in the desert of Rajasthan. Height growth data, collected over.S years, indicate a three-foldÂ· superiority of Acacia tortilis transplants over those of Acacia senegal. The rate of height growth of Acacia tortilis plants, grown out of direct seeding in trenches, has also been found to be higher than that of Acacia senegal transplants raised in pits. The relatively better performance of Acacia tortilisin this refractory site is most likely to be linked with its faster rate of root and shoot growth.